Peranan Pramuka dalam Pendidikan Anti Korupsi - Pane, Abdul Manan; Sembiring, Zamaluddin (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to examine in depth the role of the Scout Movement in supporting the implementation of anti-corruption education through character building, positive attitude habituation, and internalization of moral values in students at junior high school in Medan. The method used in this study is a descriptive qualitative approach and literature review. Anti-corruption education emphasizes the formation of self-integrity, honesty, discipline, responsibility, social concern, and the courage to reject all forms of corrupt acts. The Scout Movement was chosen as the object of study because it has a systematic, structured, and non-formal education system based on direct experience, so that values can be instilled in real terms through the daily activities of Scout members. Through the implementation of the Scout code of honor in the form of Satya and Darma Pramuka, routine training activities, leadership simulations, educational games, teamwork, social activities, and the habituation of exemplary behavior from mentors, anti-corruption education can take place in an integrative, fun, and effective manner. The study results show that active student involvement in Scouting activities can increase moral awareness, strengthen character and integrity, foster a sense of civic responsibility, and foster a firm stance against fraud and corruption from an early age.